Diabetes in Ramadhan – a comprehensive patient education program for fasting safely / Fatimah Zaherah Mohamed Shah … [et al.] - Mohamed Shah, Fatimah Zaherah; Eddy Warman, Nur ‘Aini; Awang, Mohd Hazriq; Mohamed, Aimi Fadilah; Zainordin, Nur Aisyah; Abdul Ghani, Rohana (Center for Islamic Philantrophy & Social Finance (CIPSF), 2024)
The incidence of Type2 Diabetes Mellitus (DM) in Malaysia is increasing, with 59% in Malays followed by other races. Fasting in Ramadhan with DM is challenging, requiring sufficient and comprehensive medical advice. This novel diabetes in Ramadhan patient education program aims to facilitate knowledge attainment and improve dissemination of information to mitigate the risk of complications in Ramadhan and to pave the way to fasting safely. Methods. A compilation of important information on managing the challenges DM patients face in the fasting month was assembled, gathered from the Malaysian DM clinical practice guidelines and the International Diabetes Federation (IDF) Diabetes in Ramadan Guideline. This compendium was designed mainly in the Malay language to enable better understanding in the Malaysian population. Result. This program provided comprehensive education on fasting in Ramadhan for people with DM in an engaging manner. The program was organised into three main parts: (1) patient self-educating activity; (2) specialized medical advice; and (3) lifestyle guide. This program was conducted at the UiTM Medical clinic facilities by the Endocrine team consisting of physicians and diabetic educator, and was facilitated by a specially designed educational guide, detailing important information on the risk categories for fasting in Ramadhan, timing of blood sugar monitoring, when to break the fast in the event of complication with management steps, medication adjustment, dietary advice and tips on keeping active during the fasting month. Conclusion. This innovative program has been tailored for use in the local population, and provides an essential service that is hugely beneficial, but currently lacking in this country. With this comprehensive and engaging platform, important information on managing diabetes in Ramadhan can be accessible to a wider population, leading to better patient care, and hence a has huge potential for sustainability. A larger multi-centre program will be required for a greater impact.